Trade facilitation in perishable agro-food products A feasibility study for addressing at-the-border challenges - Moïsé, Evdokia (OECD Trade Policy Papers, 2021)
Border processes for perishable agro-food products involve multiple agencies and raise complex compliance and enforcement issues. At the same time, the speed of border processes is of particular importance for exporters as delays at the border can have great negative impacts on the quality of perishable agro-food products and hence their value. This calls for a more detailed and nuanced look at the impact of trade facilitation reforms on agro-food trade. This report examines how a sub-set of OECD Trade Facilitation Indicators (TFIs) could be used to provide a more complete picture of the current performance of border processes for perishable agro-food goods. It highlights specific TFIs of relevance to agro-food, including: documentation requirements or border controls related to sanitary and phytosanitary measures and technical barriers to trade, and automation and streamlining of border formalities, and explores differentiated impacts across agro-food product groups. Practical approaches are identified to enrich the scope of the existing OECD TFIs with a view to deepening the information base on the performance of trade facilitation policies for perishable agro-food goods